Early Permian Syn-Subduction Extension in the South Tianshan (NW China): Insights From A-Type Granitoids in the Southern Altaids - Abuduxun, Nijiati; Xiao, Wenjiao; Windley, Brian F.; Huang, Peng; Yang, He; Gan, Jingmin; Sang, Miao; Liu, Xijun (Frontiers in Earth Science, 2022)
A-type granite is an important geodynamic indicator because it requires a high melting temperature that is commonly driven by extensional events. Here we report geochronology, whole-rock geochemistry, and zircon Lu-Hf isotopes of newly identified A-type granitic rocks from the South Tianshan in the southern Altaids. Zircon LA-ICP-MS ages indicate that the granitoids were emplaced at ca. 298-272 Ma. Geochemically, they are metaluminous to slightly peraluminous (A/CNK = 0.95-1.10), and belong to the high-K calc-alkaline to shoshonitic series. They are characterized by relatively high zircon saturation temperatures (824-875 ℃), K2O+Na2O contents (7.31-9.36 %), high field strength elements (HFSE; Zr + Nb + Ce + Y = 365-802 ppm), and Ga/Al ratios (2.8-4.2), which all point to an A-type affinity. In addition, they have slightly enriched Hf isotope compositions (εHf(t) = -10.9 to +0.6), and corresponding Mesoproterozoic (1272-1759 Ma) crustal model ages, suggesting they were probably generated by partial melting of mature crust that contained minor mantle-derived magmatic material. The granitoids have distinctive subduction-related trace element signatures, with deep Nb and Ta troughs, elevated large ion lithosphere elements (LILEs), and flat HFSEs patterns, very similar to arc-derived granites in the Lachlan accretionary orogen. Integration of these new sedimentological, structural and geochronological results with relevant published information provides a new data-archive, which indicates that neither the Tarim mantle plume nor post-collisional extension can explain the genesis of these A-type granitoids. Instead, we propose a new more pertinent and robust model according to which they formed due to high temperature gradient in a subduction-related extensional setting probably triggered by southward rollback of the South Tianshan oceanic lithosphere, which caused upwelling of asthenospheric mantle combined with an increased temperature that led to large-scale crustal melting. This process gave rise to a broad magmatic arc in the southern active margin of the Yili-Central Tianshan. Our new data shed light on the retreating accretionary orogenesis of the southern Altaids in the Permian.